Частота ендокринної патології у дітей із порушенням розвитку в перинатальний період за даними скринінгу - Хижняк, О. О.; Левченко, Т. П.; Черевко, І. Г.; Тихонова, Т. М.; Тамбовцева, Т. К.; Гогітідзе, Т. Г. (Clinical Endocrinology and Endocrine Surgery, 2010)
To investigate the role of birth weight (BW) in the further development of endocrinopathies retrospective screening of BW among 6150 children and teenagers with endocrinopathies, including 2454 with dysglycemias (obesity, metabolic syndrome) and 231 patients with diabetes vellitus type 1 (DM) was done. The obtained results were compared with a population random sample (596 children and teenagers of a district out-patient department). It was found out high prevalence of the endocrynopathy, including patients with DM, among children and teenagers with LGA (≥4000 g). It was not enough evidence that SGA-kids are predisposed to develop of endocrine diseases.